Two-dimensional gel proteomic analysis of Dermatophagoides farinae feces - Erban, Tomáš; Hubert, Jan (Experimental & applied acarology, 2015)
Dermatophagoides farinae fecal allergens are a major source of immunogens in home environments; however, as the source of mite fecal allergen is considered spent growth medium extract that can only mimic the pure fecal extract. In this study, we prepared and using proteomic methods analyzed a D. farinae fecal extract for the first time. The preparation approach used D. farinae feces that were produced within 8 weeks of initiating cultivation in minimized growth media. The feces were collected via adhesion to the tissue culture flask surfaces after removing the SGM and mites. This study contains in-depth proteomic mapping of the allergenic isoforms from the D. farinae fecal extract. Despite extensive analysis, MALDI TOF/TOF spectrometry showed that only six proteins/allergens, Der f1, Der f2, Der f3, Der f6, Der f15 and ferritin, originated from D. farinae. No other analyzed proteins were exactly assigned to Dermatophagoides or to similar invertebrate species by sequence similarity. The remaining proteins were assigned mostly to yeasts or cereals (originally dietary proteins); however, many of the proteins were not successfully identified in the current NCBInr. The numerous dietary proteins identified in the feces suggest that these proteins remained highly stable after passing through the gut. Isoforms of the allergens Der f1, Der f3 and Der f15 were identified in more MWs indicating the presence of zymogens and active-enzyme forms. The identified fecal allergens accumulate in the environment during the life of the mite and represent quantitatively greater amounts of mite immunogens than those that were missed in the 2D-E. The results contribute to our understanding of D. farinae digestive physiology with regard to the enzymes/proteins present in the feces.
Keywords: Animals; Dermatophagoides farinae; 2D gelová elektroforéza; Proteomics; antigeny roztočů domácího prachu; protein - isoformy; feces; zvířata; proteomika; Feces; Protein Isoforms; Electrophoresis, Gel, Two-Dimensional; Antigens, Dermatophagoides